Development of an LMS-based flipped learning e-module for TOEIC preparation - Santy Mery; Zelhendri Zen; Fetri Yeni; Rayendra Rayendra (Global Econedu, 2026)
This study aimed to develop an LMS-based e-module using the Flipped Learning model for Grade XI vocational high school students and to evaluate its validity, practicality, and effectiveness in supporting TOEIC preparation. This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The participants were 187 Grade XI students from five vocational school classes. Data were collected through expert validation sheets, student response questionnaires, and TOEIC-based pre-test and post-test assessments. Data were analyzed using descriptive statistics, normalized gain (N-Gain), paired sample t-test, Cronbach’s Alpha, and item-total correlation. The developed e-module achieved an overall validity score of 86.4%, indicating a very valid category. The practicality assessment yielded a mean score of 72.62%, categorized as practical. Students’ learning achievement improved significantly, with mean scores increasing from 26.76 (pre-test) to 63.02 (post-test). The average N-Gain score was 0.4961, indicating moderate effectiveness. Furthermore, the paired sample t-test revealed a statistically significant improvement in learning outcomes (t = 35.185, p < 0.001). The LMS-based Flipped Learning e-module is valid, practical, and effective for enhancing TOEIC-related English learning achievement among vocational high school students.